PENGARUH PENGGUNAAN APLIKASI JAKI TERHADAP PEMENUHAN KEBUTUHAN INFORMASI MENGENAI VAKSINASI COVID-19 - Vasa Salsabila (2022)
This research was motivated by the occurrence of the Covid-19 pandemic that occurred throughout the world, including in Indonesia, where people were required to get the Covid-19 vaccination as a form of prevention of virus transmission. There are still many people who are confused about finding information on the Covid-19 vaccination, therefore the DKI Jakarta Provincial Government provides information regarding the Covid-19 vaccination in the JAKI application. Fulfilling information needs in the midst of this pandemic is very necessary to prevent transmission and exposure of the virus from other people. The purpose of this study was to determine how much influence the use of the JAKI application had on meeting information needs regarding Covid-19 vaccination. The theory used in this study is the uses and gratifications theory. This research method uses a quantitative approach with the type of explanatory research, and survey research methods. The population of this study is the JAKI application users as many as 870,000 with the research sample criteria, namely active users of the JAKI application, totaling 100 respondents calculated using the Taro Yamane formula. The results of this study indicate that there is a positive influence between the use of the JAKI application on meeting information needs regarding Covid-19 vaccination by 64.5%, and the rest is influenced by other factors outside the study. The audience felt that their need for information related to Covid-19 vaccination was fulfilled after using the JAKI application. The audience strongly agrees that the JAKI application can provide and present information about vaccinations accurately. This shows that the JAKI application is an effective and influential medium in meeting the public's need for information regarding the Covid-19 vaccination.